Reviewing Energy Efficiency with the Development of Luminescent Solar Panels - Al-Sarraj, Ahmed; Salloom, Hussein T.; Oleiwi, Sahar Zaboon (International Journal of Environment, Engineering and Education, 2020)
As our fossil sources of electricity reduce consistently, then looking for alternative electricity solutions turns into crucial. Solar cells often made from expensive materials, which is why much research focused on finding cheaper materials to reduce the overall cost of solar energy. Another way to overcome this problem is to use a solar concentrator - a cheaper light-absorbing material that covers a large area, which absorbs, directs, and focuses the light to a smaller area that contains actual solar cells. The interest in exploiting solar electricity for photovoltaic energy has grown dramatically in the latest years, furthermore essential improvements inside the solar cells’ efficiency with luminescent up or down converters have currently anticipated theoretically. While solar cells are still expensive, fewer of them needed to produce a certain amount of electricity because they receive more sunlight. This paper gives, in short, evaluate the usage of luminescent solar concentrator (LSC) as opportunity electricity has low fees and comfortable as compared with photovoltaic solar panels, reviewing extra benefits in actual existence applications primarily in high structures home windows and displays of electronic devices.